1997
DOI: 10.3109/17453679708996686
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related risk factors for early revision of total hip replacements: A population register-based case-control study of 674 revised hips

Abstract: Stein E Vollset (1997) Patient-related risk factors for early revision of total hip replacements: A population register-based case-control study of 674 revised hips, Acta Orthopaedica Scandinavica, 68:3,[207][208][209][210][211][212][213][214][215]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 41 publications
5
72
1
2
Order By: Relevance
“…Analysis of the Norwegian national hip register suggested that patients who underwent THA due to femoral neck fracture 1 or those on corticosteroid medication 2 had a higher incidence of aseptic implant loosening compared to patients with THA due to osteoarthritis. The fact that femoral neck fracture and corticosteroid medication are commonly associated with weak bone suggests that a weak bone stock and regional bone loss contribute to the risk of aseptic THA loosening.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the Norwegian national hip register suggested that patients who underwent THA due to femoral neck fracture 1 or those on corticosteroid medication 2 had a higher incidence of aseptic implant loosening compared to patients with THA due to osteoarthritis. The fact that femoral neck fracture and corticosteroid medication are commonly associated with weak bone suggests that a weak bone stock and regional bone loss contribute to the risk of aseptic THA loosening.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol consumption has been associated with complications after surgery [9,16]. However, Espehaug et al [7] in a matched case-control study reported the association of alcohol intake with revision risk to be J-shaped, where the lowest risk occurred among moderate drinkers and the highest risk among patients having a consumption of more than four units/week. This type of relationship has also been established with total mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Di Castelnuovo et al [6], in a meta-analysis, found consumption of up to four drinks/day in men and two drinks/day in women was inversely associated with total mortality. Espehaug et al [7], in a matched case-control study with 674 revised hips as cases and 1343 hips as controls (primary), reported the alcohol intake association with revision risk to be J-shaped; the lowest risk was among moderate drinkers and the highest risk was among patients who consumed more than four units/week. Gmel et al [8] also found the curve depicting the consumption relationship with mortality was influenced by a combination of beneficial and harmful effects.…”
Section: Discussionmentioning
confidence: 99%
“…Results remained predictive of lower mortality after adjusting for propensity to drink and other potential confounders. Espehaug et al [8] determined patient-related factors and early risk of revision after THA performing a matched case-control study with 674 revised hips as cases and 1343 hips as controls (primary). The intake association with revision risk was found to be J-shaped; the lowest risk was among moderate drinkers and the highest among patients who consumed more than four units/week.…”
Section: Discussionmentioning
confidence: 99%